2016
DOI: 10.1007/s00267-016-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Environmental Flow Science: Developing Frameworks for Altered Landscapes and Integrating Efforts Across Disciplines

Abstract: Environmental flows represent a legal mechanism to balance existing and future water uses and sustain non-use values. Here, we identify current challenges, provide examples where they are important, and suggest research advances that would benefit environmental flow science. Specifically, environmental flow science would benefit by (1) developing approaches to address streamflow needs in highly modified landscapes where historic flows do not provide reasonable comparisons, (2) integrating water quality needs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 176 publications
1
17
0
Order By: Relevance
“…An extensive list of environmental flow frameworks has emerged (Brewer et al, ), ranging from hydrological and hydraulic frameworks to habitat simulation and more holistic approaches. Required input data at the global level are only readily available for hydrological methods.…”
Section: Methodsmentioning
confidence: 99%
“…An extensive list of environmental flow frameworks has emerged (Brewer et al, ), ranging from hydrological and hydraulic frameworks to habitat simulation and more holistic approaches. Required input data at the global level are only readily available for hydrological methods.…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest that hydrologic and hydraulic conditions experienced on the valley floor surface during out-of-bank flow may not be well represented by existing hydrologic metrics derived from discharge data alone. Additional tools are therefore needed to describe spatially explicit inundation regimes within the broader hydrologic and geomorphic contexts and assess potential responses to management activities (Bond et al 2014, Brewer et al 2016, Kozak et al 2016.…”
Section: Contribution Of 2d Hydraulic Modeling To Understanding Floodmentioning
confidence: 99%
“…For example, reintroducing high‐magnitude, long‐duration floods of a more natural flood regime may not produce positive results if the sediment to be moved by the floods is no longer present (Arthington et al, ; Wohl, Bledsoe, et al, ). Furthermore, reinstating historical flow regimes may in fact be detrimental to some ecosystems (Brewer et al, ; Palmer et al, ). A study by Tracy‐Smith et al () on Missouri River sandbar habitat showed that natural and environmental flow alternatives were less beneficial than regulated flows within the context of the channelized reach morphology of the river.…”
Section: Process‐based Thinking Drives Convergent Perspectivesmentioning
confidence: 99%